Shi'a Ideology And Its Spread In East Java - Ummu Iffah (Eduvest - Journal of Universal Studies, 2022)
This post served for see ideology and spread understand Shia as well as observe typology development understand is in East Java . Besides that this article is also presented for see why typologies understand Shia the formed . Studies this conducted with use method qualitative and approach studies case . Results show that ideology important Shia are : Imamah , Washayah , Shahadah and taqiyah . Whereas the spread of Shi'ism in East Java was centered on several the city which is pockets Shia that is Bangil , Malang, Jember , Surabaya and other areas residency of Kediri. With different social settings _ demand community Shia develop different models with other areas so that the community they can received society and survive . Typology Shia in East Java is different Among area one with area other is form adaptation and implementation from principle their taqiyah _ develop in accordance with social setting the place community that grow and develop